2010
DOI: 10.1093/her/cyq014
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel-based study of school policy for tobacco control in relation to cigarette smoking among children in elementary schools: gender differences

Abstract: The aim was to comprehensively examine school-based tobacco policy status, implementation and students' perceived smoking at school in regard to gender-specific differences in smoking behavior. We conducted a multilevel-based study to assess two-level effects for smoking among 2350 grades three to six students in 26 randomly selected elementary schools in southern Taiwan. A series of multilevel models were analyzed separately for male and female students. The school-level variables appear to be related to smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 28 publications
2
19
2
Order By: Relevance
“…Forty students (97.6%) out of 41 students who never experienced peer pressure reported as never smoked. The percentage of ever smoking students in male elementary school students in Jatinangor district was high if compared with a study conducted by Huang et al 7 in southern Taiwan. The study conducted by Huang et al 7 shows that the percentage of ever smokers in elementary school students is 13.7% in which 9.23% of them are male and 4.47% are female.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…Forty students (97.6%) out of 41 students who never experienced peer pressure reported as never smoked. The percentage of ever smoking students in male elementary school students in Jatinangor district was high if compared with a study conducted by Huang et al 7 in southern Taiwan. The study conducted by Huang et al 7 shows that the percentage of ever smokers in elementary school students is 13.7% in which 9.23% of them are male and 4.47% are female.…”
Section: Discussioncontrasting
confidence: 58%
“…The percentage of ever smoking students in male elementary school students in Jatinangor district was high if compared with a study conducted by Huang et al 7 in southern Taiwan. The study conducted by Huang et al 7 shows that the percentage of ever smokers in elementary school students is 13.7% in which 9.23% of them are male and 4.47% are female. From the total of 1,213 male students who participated in the study, 217 students (17.9%) are ever smokers and 996 students (82.1%) are never smokers.…”
Section: Discussioncontrasting
confidence: 58%
“…Five of these studies16 24 30 35 37 suggested a 20% to 60% decreased probability of tobacco use among students in schools with strict bans, supported by three studies that presented an increased risk with more liberal attitudes, especially concerning smoking by teachers 11 19 40. However, other studies failed to detect clear relationships between smoking bans per se and students’ behaviour,12 18 32 38 while one study suggested an association in the opposite direction (higher likelihood of smoking progression) if the students perceived the presence of strict bans 36…”
Section: Resultsmentioning
confidence: 95%
“…While written dissemination was linked to lower probability of smoking, the opposite association was found between formal policy and students smoking, but this was no longer observed after adjustment for individual-level variables. However, some studies failed to detect any association between formal or clearly stated school policies and students’ behaviour 17 18 34. Similarly, studies where the presence of clearly stated anti-smoking rules was self-reported by students yielded mixed results, as some found associations in the hypothesised direction26 31 37 while others did not 28 33…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation